The role of motivation in improving performance from an Islamic perspective - Alkazim, Saeed Jaffar; Battour, Mohamed (Journal of Economic, Administrative and Legal Sciences, 2021)
We concluded from this study that motivation is an important and essential part of the organizational process of the institution and that its importance lies in representing a strategy to achieve the goals of the individual and the organization together, as incentives are a development tool for the individual working in the organization. It also became necessary as it has a reflection on the quality of work and thus the abundance of production, so incentives pushed employees and workers to high levels of performance in the areas in which the stimulation methods were developed, whether material or intangible, while the pace remained terribly slow, as is the case in regions. A vast expanse of the Arab world where the wheel of production remained souls, Therefore, this study examines whether the Islamic approach to motivating workers and employees is able to be one of the most important approaches to motivating workers, and this is what the study sought, which shed light on that Islamic Sharia, as it came with tolerant teachings through which it was possible to create motives and motivate workers to work and produce other than These methods can be accessed by searching for them in the legislative texts and their interpretations, such as the Holy Qur’an and the Sunnah of the Prophet Muhammad (peace be upon him) and after studying the biography of the Prophet (may God be pleased with them) and the history of Islam.Hence, it is possible to identify the problem that the study adopted, which is the absence of a basic reference to determine the motivation, especially in the crowd of many references that are subject to political, social or economic considerations and may be inherited sometimes. It is the one who determines the methods and methods of stimulation. The criterion by which methods and tools of motivation are measured on the basis that the reference that is valid across times and places on the basis of taking into account the development of tools and the change of shapes and models, the study has reached results to this goal, and that it can be learned from the teachings of Sharia administrative materials in Field of stimulation.
Keywords: motivation; performance improvement; Islam